Good in the field and on the table - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Grown in 44 countries, chickpea (Cicer arietinum) is a highly nutritious food crop that has become an important part of the diets of many of the world s poor people. It also plays an important role in farming systems as it fits well in rotations...